The Geography Teachers' Perceptions of Various Uses of Learning Media in Public Senior High Schools in South Tangerang City - Monica Ardiani; Mushoddik Mushoddik (Universitas Muhammadiyah Kalimantan Timur, 2024)
Education is a very important and inseparable part of the process of preparing quality human resources. Education is also a conscious effort to develop the potential of human resources. To achieve optimal educational goals, there needs to be a positive interaction between the community, parents and the school. The development of technology has had a significant impact on education, with the accessibility of information made easier by the internet and digital resources, changing the way we learn and access knowledge. In this study, the main objective is to analyze geography teachers' perceptions of the various uses of learning media in public high schools in South Tangerang City. This research is descriptive research using the survey method. Data analysis was conducted using descriptive statistical analysis methods, specifically percentage analysis. By using percentages, this study can analyze the level of geography teachers' perceptions of the various uses of learning media in public high schools in South Tangerang City. The results showed that the perception of geography teachers in public high schools in South Tangerang City towards the use of various learning media is in the very good category, with a percentage reaching 94%. This finding shows that geography teachers in public high schools in South Tangerang City have a very positive perception of the use of learning media.